Cash Business in England (Quarterly Journal of Economics, 1887)
Cash Business in England The Quarterly Journal of Economics, Volume 2, Issue 1, October 1887, Pages 67–68, https://doi.org/10.1093/qje/2.1.67 Published: 01 October 1887